2004
DOI: 10.1128/jb.186.15.4894-4902.2004
|View full text |Cite
|
Sign up to set email alerts
|

A Novel p -Nitrophenol Degradation Gene Cluster from a Gram-Positive Bacterium, Rhodococcus opacus SAO101

Abstract: p-Nitrophenol (4-NP) is recognized as an environmental contaminant; it is used primarily for manufacturing medicines and pesticides. To date, several 4-NP-degrading bacteria have been isolated; however, the genetic information remains very limited. In this study, a novel 4-NP degradation gene cluster from a gram-positive bacterium, Rhodococcus opacus SAO101, was identified and characterized. The deduced amino acid sequences of npcB, npcA, and npcC showed identity with phenol 2-hydroxylase component B (reductas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
117
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 160 publications
(122 citation statements)
references
References 32 publications
4
117
0
1
Order By: Relevance
“…5 and Table 2) also contributes to the general understanding of reactions of its homologs identified by SSN analysis (supplemental Fig. S1) (9,10,13,(33)(34)(35). These enzymes were identified in microbes that showed potential in bioremediation applications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 and Table 2) also contributes to the general understanding of reactions of its homologs identified by SSN analysis (supplemental Fig. S1) (9,10,13,(33)(34)(35). These enzymes were identified in microbes that showed potential in bioremediation applications.…”
Section: Discussionmentioning
confidence: 99%
“…S1) showed that there are 2,839 enzymes in which the sequences have Ͼ34% identity with HadA, and only 11 of these 2,839 enzymes were reviewed by UniProt. The enzymes identified to be homologous to HadA were mostly flavin-dependent monooxygenases that incorporate a hydroxyl group into phenols such as CPs or nitrophenols (9,10,(33)(34)(35). As these enzymes showed potential applications in bioremediation of toxic compounds, the understanding of kinetic mechanisms associated with a flavin-dependent dechlorinase (HadA) reported herein should also be useful for giving an overall picture about the reaction mechanism of these enzymes in general.…”
mentioning
confidence: 99%
“…Other genera in the phylum Actinobacteria, such as Actinomadura 2) , Arthrobacter 8) , and Nocardia 23) have also been reported to produce antibiotics, though they have not been studied extensively. In the last few decades, the genus Rhodococcus, a member of Actinobacteria, has received considerable attention for its remarkable ability to degrade persistent chemicals such as polychlorinated biphenyls (PCBs) 14,15) and nitrophenols 4,11) ; the industrial application of nitrile hydratase that is synthesized by the members of this genus 13) has also been investigated. Previous research has also focused on the plant and mammalian pathogenic characteristics of some species belonging to this genus 3,16) .…”
mentioning
confidence: 99%
“…42) It has been reported that S. wittichii RW1 has multiple copies of the terminal dioxygenase subunit gene for AhDO, 43) and there is a possibility that these uninvestigated AhDOs affect dioxin degradation in RW1 cells. Also, it has been shown that R. opacus SAO101 can utilize diverse aromatic compounds, 44) and therefore might have multiple AhDO genes with different specificities in addition to narAaAb genes, 45) as reported for some diverse aromatics-degrading actinomycetes, such as Rhodococcus jostii RHA1, 46) R. erythropolis TA421, 28) and Mycobacterium vanbaalenii PYR-1.…”
Section: Ahdo-expressing Rhodococcus Sp Rd2 Depleted Chlorinated Diomentioning
confidence: 99%